Pesticide Poisoning and the Use of Personal Protective Equipment (PPE) in Indonesian Farmers. (21st January 2020) - Joko, Tri; Dewanti, Nikie A. Y; Dangiran, Hanan L.
Abstract : This study aimed to investigate the poisoning symptoms occurring in pesticide-exposed farmers. This study was conducted in a red onion farming center area in Wanasari Subdistrict, Brebes, Indonesia, from May to June 2018. This study was designed as the descriptive study. The significance value of p < 0.005 showed that the variable was correlated with the health problems, including excessive fatigue (p value = 0.041), excessive saliva (p value = 0.006), hard breathing (p value = 0.021), frequent urination (p value = 0.047), blurred vision (p value = 0.059), dizziness (p value = 0.032), and finger pain (p value = 0.007). The significance value (p < 0.005 ) of 0.000 showed that the use of personal protective equipment was correlated with the health problems. Based on the odds ratio value of 1.137, 95% confidence interval = 0.042–0.444 meant that the personal protective equipment was a risk factor of health problems. The results showed that 89.2% of the farmers who used the personal protective equipment were categorized in the healthy group.